Comparing the outcome between multicentric/multifocal breast cancer and unifocal breast cancer: A systematic review and meta-analysis - Zhang, Yalan; Liu, Fan; Gao, Qianqian; Chai, Yahui; Ren, Yan; Tian, Hongyou; Ma, Bin; Song, Ailin (Frontiers in Oncology, 2022)
Abstract Objective: This systematic review and meta-analysis compares the outcome between MMBC and unifocal breast cancer (UFBC), in order to provide a theoretical basis for the design of an appropriate clinical therapeutic strategy of MMBC patients. Methods: PubMed, Embase, The Cochrane Library, Web of science, CNKI, WanFang Data, CBM and VIP database were searched from inception to July 2021, and observational studies reporting the outcome of patients with MMBC and UFBC were included. We extracted or calculated the mortality rates of MMBC and UFBC patients; and obtained the hazard ratios; odds ratios; relative risks; and the corresponding 95% confidence intervals from the eligible studies. All the meta-analyses were conducted by using the Stata 15.0 software. Results: 31 eligible studies comprising a total of 15,703 individuals were included. The meta-analysis revealed that MMBC did not have a significant association with poor overall survival (HR=1.04, 95% CI=0.96-1.12), disease-free survival (HR= 1.07, 95% CI= 0.84-1.36), breast cancer-specific survival (HR=1.42, 95% CI= 0.89-2.27), recurrence-free survival (HR= 0.878, 95% CI= 0.652-1.182), local recurrence-free survival (HR= 0.90, 95% CI= 0.57-1.42), and contralateral breast cancer risk (RR= 0.908, 95% CI= 0.667-1.234). However, MMBC appeared to have a correlation with a slightly higher risk of death (OR=1.31, 95% CI=1.18-1.45). Conclusion: Patients with MMBC appeared to have a higher risk of death, however, it may not be independently associated with poorer outcomes. Considering the inter-study heterogeneity and other limitations, our results need to be validated by further multicenter prospective studies with a large sample size in the future.